The reception of blackness in Portuguese-speaking Africa - (:unkn) unknown (My University, 2015)
This thesis studies how Négritude was received in Portuguese-speaking Africa. In order to achieve this, the study addresses the origins of Négritude through the poets and writers of the Harlem Renaissance as well as René Maran’s Batouala. This permits a better discussion of the emergence of the concept of Négritude through Aimé Césaire, Léon Gontran Damas and Léopold Sedar Senghor. The study analyses the ideology of Négritude and the poets’ struggle for the freedom of black peoples and those oppressed by colonialism. Finally, this research examines the impact of the reception of Négritude on the African Lusophone literature of Agostinho Neto, José Craveirinha and Noémia de Sousa. Did it contribute to freeing the colonies of Portuguese-speaking Africa from colonial oppression and to strengthening the quest for identity? This study seeks to show that the humanism of Négritude returns us to a tribute to the human condition and the promise of possibility.
Keywords: African Research